Efektivitas Implementasi Pelatihan Keterampilan Kerja Dalam Meningkatkan Kompetensi Calon Tenaga Kerja - Muhammad Arief Rizka; Zulkipli Zulkipli (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2017)
This study aims to analyze the effectiveness level of the implementation of working skill trainingprograms in the field of office administration in improving the competence of prospective workers in theTraining Center (BLK) Mataram City. This research is an evaluative research by using quantitative descriptivemethod. The research instrument used is a questionnaire. Data analysis technique used in this research isdescriptive statistical analysis. The results of this study indicated that the training implementation processaspect with the training instructor role indicator got the percentage 82.73%, the training material indicator was78.76%, the training method indicator was 79.76%, while the result aspect follows the training with thecognitive domain indicator got the percentage 84, 92%, the affective field indicator was 81.34%, psychomotordomain indicator was 79.16%, while achievement goal aspect after work skill training got percentage 82,03%.Thus, it can be concluded that the effectiveness of the implementation of working skill training programs in thefield of office administration in improving the prospective workers competence in the Training Center (BLK)Mataram has been effectively implemented.